Enhanced performance feedback and patient participation to improve hand hygiene compliance of health-care workers in the setting of established multimodal promotion: a single-centre, cluster randomised controlled trial. Issue 12 (December 2016) - Stewardson, Andrew James; Sax, Hugo; Gayet-Ageron, Angèle; Touveneau, Sylvie; Longtin, Yves; Zingg, Walter; Pittet, Didier
Summary: Background: Hand hygiene compliance of health-care workers remains suboptimal despite standard multimodal promotion, and evidence for the effectiveness of novel interventions is urgently needed. We aimed to assess the effect of enhanced performance feedback and patient participation on hand hygiene compliance in the setting of multimodal promotion. Methods: We did a single-centre, cluster randomised controlled trial at University of Geneva Hospitals (Geneva, Switzerland). All wards hosting adult, lucid patients, and all health-care workers and patients in these wards, were eligible. After a 15-month baseline period, eligible wards were assigned by computer-generated block randomisation (1:1:1), stratified by the type of ward, to one of three groups: control, enhanced performance feedback, or enhanced performance feedback plus patient participation. Standard multimodal hand hygiene promotion was done hospital-wide throughout the study. The primary outcome was hand hygiene compliance of health-care workers (according to the WHO Five Moments of Hand Hygiene) at the opportunity level, measured by direct observation (20-min sessions) by 12 validated infection control nurses, with each ward audited at least once every 3 months. This trial is registered with ISRCTN, number ISRCTN43599478. Findings: We randomly assigned 67 wards to the control group (n=21), enhanced performance feedback (n=24), or enhanced performance feedback plus patient participation (n=22) on May 19, 2010. One ward in the control group became a high-dependency unit and was excluded from analysis. During 1367 observation sessions, 12 579 hand hygiene opportunities were recorded. Between the baseline period (April 1, 2009, to June 30, 2010) and the intervention period (July 1, 2010, to June 30, 2012), mean hand hygiene compliance increased from 66% (95% CI 62–70) to 73% (70–77) in the control group (odds ratio [OR] 1·41, 95% CI 1·21–1·63), from 65% (62–69) to 75% (72–77) in the enhanced performance feedback group (1·61, 1·41–1·84), and from 66% (62–70) to 77% (74–80) in the enhanced performance feedback plus patient participation group (1·73, 1·51–1·98). The absolute difference in compliance attributable to interventions was 3 percentage points (95% CI 0–7; p=0·19) for the enhanced performance feedback group and 4 percentage points (1–8; p=0·048) for the enhanced performance feedback plus patient participation group. Hand hygiene compliance remained significantly higher than baseline in all three groups (OR 1·21 [1·00–1·47] vs 1·38 [1·19–1·60] vs 1·36 [1·18–1·57]) during the post-intervention follow-up (Jan 1, 2013, to Dec 31, 2014). Interpretation: Hand hygiene compliance improved in all study groups, and neither intervention had a clinically significant effect compared with control. Improvement in control wards might reflect cross-contamination, highlighting challenges with randomised trials of behaviour change. Funding: Swiss National Science Foundation.